Structural Patterns Of Knot Semantic Logic In Mbojo Pantun - Ja'faruddin Ja'faruddin; M. Fadly; Khaerati Khaerati (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
Mbojo Pantun (Patu Mbojo) is an important form of indigenous oral literature that preserves cultural values, moral teachings, and local wisdom within the Bima community of West Nusa Tenggara, Indonesia. While previous studies have primarily examined Mbojo Pantun from linguistic, literary, and cultural perspectives, its underlying mathematical semantic organization remains largely unexplored. This study aims to investigate the structural patterns of Mbojo Pantun using the Knot Semantic Logic (KSL) framework. A qualitative descriptive approach was employed by selecting representative pantun through purposive sampling from documented literary sources and oral traditions. The analysis involved identifying semantic knot points, constructing knot point matrices, examining recursive semantic correspondences, and classifying structural configurations according to the principles of Knot Semantic Logic. The results identified four semantic structures: Ring Composition, Chiasm, Parallelism, and Asymmetrical Semantic Structure (ASS). Ring Composition exhibits concentric semantic symmetry centered on a core concept, Chiasm demonstrates mirrored semantic correspondence, and Parallelism preserves sequential semantic repetition. In contrast, Asymmetrical Semantic Structure represents a linear progression of ideas without recursive semantic correspondence. These findings demonstrate that the semantic organization of Mbojo Pantun can be formally represented through mathematical structures, revealing that indigenous oral literature embodies systematic semantic patterns beyond its aesthetic and cultural functions. Furthermore, this study extends the application of Knot Semantic Logic from formal statements and religious discourse to traditional oral literature and proposes Asymmetrical Semantic Structure (ASS) as a complementary structural category within the KSL framework. The proposed framework contributes to the development of mathematical linguistics, ethnomathematics, and computational approaches to semantic structure analysis.